The Smoking Phenomenon in Gen Z: A Review of Health Analyses, Social Influences, and Educational Prevention Strategies - A. Muh. Fathul Rahman; St. Nurhayati (Cendekiawan : Jurnal Pendidikan dan Studi Keislaman, 2024)
This study aims to analyse the health impacts, social influences, and prevention strategies of the smoking phenomenon in gen Z. The method used in this research is a qualitative approach with a literature study method. The results of this study reveal that although awareness of the dangers of smoking has been widespread in society including Gen-Z, many of them continue to smoke for various reasons, including increased focus, stress relief, and even social acceptance among students. As a solution, collaboration from various parties, including the government, educational institutions, families, and health organisations, is needed to create an environment that supports a healthy lifestyle among Gen-Z. The government and health institutions are advised to expand anti-smoking campaigns to include positive alternatives for managing stress, such as exercise, yoga and counselling. In addition, schools and colleges are expected to conduct educational programmes on stress management and smoking risks through seminars, workshops or digital platforms that appeal to Gen Z. The role of the family is also important to provide supervision and support with open communication about the dangers of smoking. A comprehensive approach, including social support, education, and health campaigns, is expected to increase young people's awareness of the risks of smoking and encourage them to choose a healthy lifestyle without dependence on cigarettes.